Adsorption behaviors on trace Pb2+ from water of biochar adsorbents from konjac starch. Issue 9 (December 2020) - Li, Yinhui; Peng, Longfei; Li, Weixin
Biochar adsorbents used to treat different heavy metals in water are efficient and low-cost. Appropriate raw materials, excellent selectivity and detailed adsorption mechanism are of important for research on biochar adsorbents. In this work, konjac starch was dispersed in polyvinylpyrrolidone (PVP) solution to prepare different sizes hydrophilic carbon spheres (HCSs) by hydrothermal synthesis method. Adsorption kinetics of the HCSs towards Pb 2+ is described perfectly by the pseudo-second-order equation. With the temperature increasing, adsorption thermodynamics are more consistent with the Freundlich model. The calculated ΔG, ΔH and ΔS shows the adsorption of the HCSs towards Pb 2+ is a spontaneous, endothermic and entropy increase process. In addition, HCSs have excellent selectivity for the adsorption of Pb 2+ and Cu 2+ . HCSs prepared from konjac starch make full use of natural biomass resources, they can be used as a potential adsorbent material in treatment on heavy metal ion from water field.